2020
DOI: 10.3390/f11030358
|View full text |Cite
|
Sign up to set email alerts
|

Short Legacy Effects of Growing Season Nitrogen Addition and Reduced Precipitation alter Soil Respiration during Nongrowing Season

Abstract: The short legacy effects of growing season nitrogen (N) addition and reduced precipitation on nongrowing season soil respiration (Rs), autotrophic respiration (Ra), and heterotrophic respiration (Rh) are still unclear. Therefore, a field manipulative experiment to determine the responses of nongrowing season Rs and its components to growing season N addition and reduced precipitation was conducted in a temperate forest. The results show that growing season N addition and reduced precipitation significantly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The estimation of Q 10 values support this speculation; long‐term reduction of the precipitation amount significantly decreased Q 10 within our soils throughout the drought experiment. This is in line with Yan et al (2020), who also observed lower Q 10 as a response to reduced precipitation in the previous year before sampling. However, more field studies targeting legacy effects on microbial C allocation during drought and after rewetting are needed to improve our mechanistic understanding of historical precipitation regimes’ influence on the effects of soil warming.…”
Section: Discussionsupporting
confidence: 92%
“…The estimation of Q 10 values support this speculation; long‐term reduction of the precipitation amount significantly decreased Q 10 within our soils throughout the drought experiment. This is in line with Yan et al (2020), who also observed lower Q 10 as a response to reduced precipitation in the previous year before sampling. However, more field studies targeting legacy effects on microbial C allocation during drought and after rewetting are needed to improve our mechanistic understanding of historical precipitation regimes’ influence on the effects of soil warming.…”
Section: Discussionsupporting
confidence: 92%
“…Q 10 , the temperature sensitivity index for Rs, refers to the ratio between the value of Rs at a given temperature to its value at a temperature 10 • C lower than the given temperature. Q 10 is generally expressed as follows [2,41]:…”
Section: Discussionmentioning
confidence: 99%
“…where b is the fitted parameter obtained from Equation (2). A one-way ANOVA analysis followed by post hoc LSD tests were performed to determine the differences in the effect size of Rs between groups in each stand age in the whole study period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations